The Effect of Service Quality, Image, Motivation on Loyalty Through Satisfaction in Women's Cooperatives (Universitas Negeri Semarang, 2022)
This study aims to determine whether the level of loyalty of members of women's cooperatives in Tulungagung Regency still needs to be improved so that the performance of women's cooperatives in the future increases and the goals of women's cooperatives will be achieved. The population in this study is the Women's Cooperative which carries out RAT and SHU distribution for 2 consecutive years (2020 – 2021) and the number of cooperative members is above 100 people, so there are 5,415 members from 36 women's cooperative units. The sample used was 358 members from 18 women's cooperatives, using proportional random sampling. Data analysis used descriptive analysis, classical assumption test, path analysis, and Sobel test. The results of hypothesis testing showed that there was a positive and significant effect on service quality, cooperative image, while cooperative motivation on member loyalty. There is a positive and significant effect of service quality on member loyalty through member satisfaction and cooperative image on member loyalty through member satisfaction, while cooperative motivation on member loyalty through member satisfaction and there is an effect of member satisfaction on member loyalty at the Women's Cooperative Tulungagung Regency.